Synthesis of diatomite/Fe3O4/Teff straw activated carbon composite adsorbent for Cr(VI) removal from wastewater - Sintayehu Shewatatek; Girma Gonfa; Sintayehu Mekuria; Belete Tessema; Gulmira Kezembayeva; Kalyan Sundar Ghosh; Muhammad Mushtaq; Mohammad Hadi Diyanatizadeh; Kaan Isinkaralar; Ahmad Hosseini-Bandegharaei (Results in Chemistry)
Heavy metal pollution, particularly chromium (Cr), poses a significant environmental challenge. This study addresses this issue by developing a novel composite adsorbent consisting of diatomite (DE), Fe3O4, and an activated carbon from teff straw (TSAC). The nanocomposite was characterized, exploiting FT-IR, BET, SEM, and XRD analyses, revealing a substantial BET surface area of 347.45 m2/g. Response surface methodology (RSM) with central composite design (CCD) was exploited to optimize adsorption parameters, including pH, adsorbent dose, initial Cr(VI) concentration, and adsorption time. Optimal conditions yielded a removal efficiency of 93.28 % at pH 4, an adsorbent dose of 0.024 g/100 mL, an initial Cr(VI) level of 15 mg/L, and an adsorption time of 60 min. The results showed that the Freundlich and Langmuir isotherm models, along with Toth model, best matched the data. This implies that both monolayer and heterogeneous surface adsorptions are the main mechanism, with a maximal sorption capacity of 131 mg/g and followed the pseudo-second-order kinetic model. Thermodynamic analyses uncovered the spontaneous and endothermic nature of the Cr (VI) adsorption by DE/Fe3O4/TSAC. The composite's recyclability was demonstrated over five cycles, maintaining significant removal efficiency. Such findings highlight the potentials of the DE/Fe3O4/TSAC composite for effective Cr (VI) removal from water, offering a promising solution to mitigate chromium pollution.